2017
DOI: 10.1111/resp.13095
|View full text |Cite
|
Sign up to set email alerts
|

Continuous non‐invasive PCO2 monitoring in weaning patients: Transcutaneous is advantageous over end‐tidal PCO2

Abstract: Our data therefore support PtcCO as a suitable means for monitoring PCO in patients undergoing invasive MV. This is in contrast to PetCO , which clearly underestimated PaCO , especially in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Finally, uncontrolled nocturnal hypoventilation seems to be related to increased risk of exacerbations and pulmonary hypertension [121]. End tidal carbon dioxide monitoring should never be used to approximate P aCO 2 in patients with COPD during spontaneous breathing or NIV, and is even less reliable in patients with invasive ventilation [122,123] In recent years, improvements introduced by manufacturers in their models have led these devices to act both as ventilators and monitors. Data stored in the internal memory of such devices provide information about compliance, pattern of usage, respiratory rate, percentage of patient triggered breaths, leakage and, in some models, "breath to breath" display of pressure and flow time waveforms.…”
Section: Narrative Question 2: How Can Clinicians Monitor and Follow-mentioning
confidence: 99%
“…Finally, uncontrolled nocturnal hypoventilation seems to be related to increased risk of exacerbations and pulmonary hypertension [121]. End tidal carbon dioxide monitoring should never be used to approximate P aCO 2 in patients with COPD during spontaneous breathing or NIV, and is even less reliable in patients with invasive ventilation [122,123] In recent years, improvements introduced by manufacturers in their models have led these devices to act both as ventilators and monitors. Data stored in the internal memory of such devices provide information about compliance, pattern of usage, respiratory rate, percentage of patient triggered breaths, leakage and, in some models, "breath to breath" display of pressure and flow time waveforms.…”
Section: Narrative Question 2: How Can Clinicians Monitor and Follow-mentioning
confidence: 99%
“…The Severe Respiratory Insufficiency Questionnaire (SRI) was designed and validated for HRQL in patients receiving long-term NIV therapy [27, 28]. Transcutaneous PCO 2 (PtcCO 2 ) (SenTec Digital Monitoring System; VStats-Software®: 4.00; SenTec AG, Therwil, Switzerland) measurements were performed during daytime ventilation in selected patients [29, 30]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, PtcCO 2 monitoring is also suggested to be superior over end tidal PCO 2 monitoring because ventilation-perfusion mismatching regularly occurring in ICU patients is suggested to distort PCO 2 measurements when using end tidal monitoring [32][33][34]. However, there was a significant range of the limits of agreement between arterial and transcutaneous PCO 2 measurements in the present study, a range which was even somewhat higher than previously reported in patients receiving mechanical ventilation [32][33][34]. This observation may be attributed to the special clinical scenario with high individual stress levels when performing the intervention and catecholamine treatment.…”
Section: Discussionmentioning
confidence: 99%